2016
DOI: 10.20960/nh.796
|View full text |Cite
|
Sign up to set email alerts
|

Análisis del grado de satisfacción alimentaria percibido por los pacientes en un hospital de tercer nivel

Abstract: Análisis del grado de satisfacción alimentaria percibido por los pacientes en un hospital de tercer nivel Assessment of the level of alimentary satisfaction received by patients in a tertiary hospital AbstractIntroduction: Food is a key element of nutritional support of hospitalized patients. To assess the level of food acceptance is essential to fi ght hospitalary malnutrition. Aims: a) To determine the level of satisfaction of patients to our diets; and b) to analyse variables associated with a higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
(36 reference statements)
0
3
0
1
Order By: Relevance
“…On the other hand, although the hospital diet is not always well received by patients, nevertheless, those who presented COVID-19 reported better satisfaction with the diet (gastronomic experience) during the hospital stay. It is worth mentioning that similar studies [21][22][23][24][25] conducted in patients without COVID-19, found that hospitalized patients reported high levels of satisfaction with the hospital diet. These results could indicate the adequate progress in the quality of care by the nutrition service staff and with the diet served.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…On the other hand, although the hospital diet is not always well received by patients, nevertheless, those who presented COVID-19 reported better satisfaction with the diet (gastronomic experience) during the hospital stay. It is worth mentioning that similar studies [21][22][23][24][25] conducted in patients without COVID-19, found that hospitalized patients reported high levels of satisfaction with the hospital diet. These results could indicate the adequate progress in the quality of care by the nutrition service staff and with the diet served.…”
Section: Discussionmentioning
confidence: 86%
“…Likewise, the degree of satisfaction with respect to hospital diets (complete or therapeutic) has been evaluated by some authors to include improvements in nutritional care processes, but without relating them to the variables described above. [21][22][23][24][25] Several investigations that studied the percentage of food waste of the hospital diet to quantify the intake or determine the acceptability of the diets served, resulted in an average value between 30-40%, which has a direct effect on the nutritional status of the patient. 15,[26][27][28][29] In a study of nutritional therapy in hospitalized patients by COVID-19, nutritional intake was found to be at the lower limit or below the recommended amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Some factors that may explain the high rates of disease-related malnutrition and dysphagia are the lack of means and the scarcity of information on nutrition by professionals [ 13 ], as well as the quality of the food offered in hospitals [ 19 ]. The level of acceptance of hospital food has an important relationship with the user’s overall satisfaction and quality of life during admission [ 20 ]. Thus, the assessment of the quality of menus during hospital admission and patient satisfaction is considered an appropriate method of nutritional assessment in patients at risk of malnutrition and dysphagia [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Es un resultado a alcanzar dentro de lo establecido legalmente, dentro del derecho a la atención de la salud de toda la población y como misión del Sistema Nacional de Salud, que es un Sistema Único, Estatal, Integral y Gratuito. (Benítez et al, 2016(Benítez et al, , p. 1362.…”
unclassified